Platelet phenotype changes associated with breast cancer and its treatment. (2nd October 2016) - Holmes, Chris E.; Levis, Jamie E.; Schneider, David J.; Bambace, Nadia M.; Sharma, Deva; Lal, Inder; Wood, Marie E.; Muss, Hyman B.
Abstract: Platelets and their granular contents influence both angiogenesis and breast cancer progression. This study was performed to assess the effect of breast cancer and its treatment on platelet biology and the response to inhibition of the platelet P2Y12 receptor. Receptor-specific platelet activation and inhibition was studied for three platelet-associated proteins important in cancer angiogenesis and progression, vascular endothelial growth factor (VEGF), thrombospondin1 (TSP1), and transforming growth factor beta 1 (TGF-β1). Twenty-four women with active breast cancer and 10 healthy controls not receiving antiplatelet therapy participated in the study. Ex vivo activation of platelets in whole blood was accomplished using PAR1AP, PAR4AP, convulxin, and ADP. Platelet inhibition was accomplished using the P2Y12 receptor antagonist cangrelor (the in vitro equivalent of clopidogrel). VEGF, TSP1, and TGF-β1 were measured using standard ELISA. Platelet activation by ADP, PAR1, PAR4, and collagen receptors increased VEGF, TSP1, and TGF-β1 secretion in patients with breast cancer. Agonist-induced release of VEGF was greater in cancer patients as compared to healthy controls ( p = 0.02 for ADP, p < 0.001 for PAR1AP, PAR4AP, and convulxin) despite a decrease in the efficiency of VEGF secretion in patients with breast cancer. These differences were not observed for TSP1 and TGF-β1 secretion. P2Y12 receptor inhibition decreased VEGF, TSP1, and TGF-β1 secretion. In patients with cancer, cangrelor inhibited TSP1 release to a greater extent than VEGF and TGF-β1 release. In patients with breast cancer, the magnitude of platelet inhibition achieved by cangrelor was greater than that achieved with healthy controls for all agonists and platelet proteins studied. While platelets are known to influence progression of breast cancer, our results show that breast cancer and its treatment influence the platelet phenotype by increasing the secretion of pro-angiogenic proteins following platelet activation, modulating the efficiency of platelet protein release as well as increasing the response to antiplatelet therapy.